2022
DOI: 10.1177/03000605221133689
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between clinical trials and real-world evidence studies on biologics for severe asthma

Abstract: In recent years, the more widespread availability of biological drugs with specific mechanisms of action has led to significant breakthroughs in the management of severe asthma. Over time, numerous randomised clinical trials have been conducted to evaluate the efficacy and safety of these biologics and define the eligibility criteria of patients suitable for various therapeutic options. These studies were conducted under controlled conditions not always applicable to real life. For this and other reasons, real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 127 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…A global, prospective, observational cohort study, REALITI-A, showed that real-world rates of CSEs were reduced by 71% with mepolizumab treatment, as were exacerbations requiring hospitalizations and/or ED visits (76% reduction), while median daily oral corticosteroid (OCS) dose (in patients using maintenance OCS) decreased by 75% (10 mg/day to 2.5 mg/day) after 1 year of treatment [ 6 ]. Further studies have supported these findings, including the real-world REDES study in Spain, where mepolizumab reduced CSEs in patients with SA-EP by up to 77.5% compared to baseline [ 7 9 ]. Whilst a strength of REALITI-A was its multi-national study design, evaluation in a variety of real-world populations within different healthcare systems is invaluable.…”
Section: Introductionmentioning
confidence: 89%
“…A global, prospective, observational cohort study, REALITI-A, showed that real-world rates of CSEs were reduced by 71% with mepolizumab treatment, as were exacerbations requiring hospitalizations and/or ED visits (76% reduction), while median daily oral corticosteroid (OCS) dose (in patients using maintenance OCS) decreased by 75% (10 mg/day to 2.5 mg/day) after 1 year of treatment [ 6 ]. Further studies have supported these findings, including the real-world REDES study in Spain, where mepolizumab reduced CSEs in patients with SA-EP by up to 77.5% compared to baseline [ 7 9 ]. Whilst a strength of REALITI-A was its multi-national study design, evaluation in a variety of real-world populations within different healthcare systems is invaluable.…”
Section: Introductionmentioning
confidence: 89%
“…Asthma is a disease characterised by a great heterogeneity of immunological pathways and clinical manifestations, and it requires an approach based on personalised medicine and the study of phenotypes and endotypes [ 1 , 2 ]. Over the past 20 years, biological drugs have been developed for the treatment of severe refractory asthma, with numerous randomised controlled trials (RCTs) conducted to define their safety and efficacy [ 3 ]. These drugs have targeted mechanisms of action and are addressed to specific patients, albeit there is a certain degree of overlap regarding their inflammatory characteristics—especially those with type 2 (T2)-high asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Omalizumab works by inhibiting the interaction between human IgE and the high- and low-affinity receptors [ 8 ]. Numerous studies have demonstrated the effectiveness of omalizumab in improving different clinical parameters of severe asthma and providing better control of disease exacerbation and airflow obstruction [ 9 11 ]. However, some patients have a poor response to omalizumab and require alternative biologic therapies [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%